Piezotronic effect determined neuron-like differentiation of adult stem cells driven by ultrasound. (December 2021) - Liang, Linlin; Sun, Chunhui; Zhang, Ruitong; Han, Shuwei; Wang, Jingang; Ren, Na; Liu, Hong
Abstract: Electrical stimulation is an efficient approach to inducing neural differentiation of stem cells. However, most demonstrations of conventional electrical stimulation for the regulation of stem cell differentiation generally involve three components—an electrical signal generator, conductive culture substrate, and pair of lines, which limits its use in clinical applications for neural degeneration treatments. Herein, we proposed a facile method to generate localized electrical signals on the surface of a piezoelectric poly (vinylidene fluoride) (PVDF) film with a well-designed nanopillar array driven by ultrasound irradiation based on a piezotronic effect, which proved to induce neuronal differentiation of rat bone marrow mesenchymal stem cells (rBMSCs) without any biological or chemical neural inducing factors. The assessment of rBMSCs on the surface of the PVDF nanopillar array at the gene and protein levels confirmed that rBMSCs could differentiate into neuron-like cells. This demonstration provides a practical approach for the regulation of adult stem cells to differentiate into neurons, which will be a great achievement to overcome the shortage of neural stem cells in the adult human body and realize the autologous stem cell treatment of neurodegeneration. This work creates a new therapeutic avenue for contactless, controlled neuroregenerative therapies. Graphical Abstract: Ultrasonic driven PVDF nanopillar array in situ generate strong wireless electrical signals based on piezotronic effect can effectively manipulate the rBMSCs differentiated into neuron-like cells. ga1 Highlights: PVDF nanopillars were prepared by a facile hot-pressing method with AAO template. Ultrasonic driven PVDF nanopillar array have excellent piezoelectric generation. Wireless electrical signals induce neuron-like differentiation of adult stem cells. No neuroinducible factors were added during neuron-like differentiation.